Assessment of peroral intake of nitrates with drinking water for different sections of the population of Zhytomyr region (Environment & Health, 2022)
Objective: We assessed the degree of risk to the health of the rural population of different ages with constant peroral intake of nitrates with drinking water.Materials and methods: The study was conducted within the rural residential areas of Zhytomyr region and it is a part of the research "Ecological and social assessment of the state of rural residential areas in the context of sustainable development." Drinking water samples were taken from public and private sources of decentralized water supply: wells, bore-wells and natural sources. A total 549 water samples were taken. In the study, we used general scientific methods: analytical, field, laboratory and statistical ones.Results: Among the studied areas, the largest excess of the average content of nitrates was recorded in drinking water of rural settlements of Berdychiv district. The risk assessment showed that the children aged 0-10 years were the most sensitive population to nitrates, and the women were more vulnerable to nitrates than the men among the adult population. The significant correlations between an excess of nitrate content in drinking water and cancer among adults and children in Berdychiv district have been proven.Conclusions: It has been proven that with a constant oral intake of nitrates with drinking water, harmful effects on the health of the rural population are observed, which, according to their sensitivity to their action, were distributed as follows: children 0-10 years old> adult women> adult men> adolescents.Taking into account the results obtained, it is necessary to monitor constantly the quality of drinking water sources of decentralized water supply in rural areas and to inform the rural population about water quality and the impact of its impurities on human health.
Keywords: drinking water; sources of decentralized water supply; rural settlements; nitrates; risk; health of the population